Satellite-Based Time Series of Chlorophyll in Chilko Lake, British Columbia, Canada - Leslie N. Brown; Gary A. Borstad; Kaan Ersahin; Eduardo Loos; Daniel Selbie; Maycira Costa; James R. Irvine (Canadian Journal of Remote Sensing, 2019)
In Canada, many northern lakes are remote and difficult to access, with limited limnological data. Satellite sensors provide widespread coverage and growing time series of data unavailable via conventional sampling, but global validation is still limited. We evaluated chlorophyll estimates from the MERIS (Medium Resolution Imaging Spectrometer) sensor on board the European Space Agency (ESA) ENVISAT satellite for the ultra-oligotrophic Chilko Lake in the coastal mountains of central British Columbia. This lake supports a valuable sockeye salmon (Oncorhynchus nerka) population. We obtained good temporal coverage, through 1,425 scenes between June 18, 2002 and April 6, 2012. Although pre-processing was required to produce a high-quality dataset, one standard ESA algorithm generated chlorophyll estimates similar to field data. Regional and interannual phenological patterns were clear, and differences that may be important determinants of salmon production were well described. Although MERIS ceased operation in April 2012, it was replaced by the OLCI (Ocean and Land Color Instrument) on the SENTINEL 3a and 3b satellites launched in February 2016 and April 2018, respectively. We conclude that, with appropriate quality control and in situ validation, satellite-generated chlorophyll time series in sockeye salmon rearing lakes have significant potential as a fisheries planning and analysis tool.